Green potential from palm biomass in Malaysia - Lam, H.; Ng, Wendy; Ng, F.; Kamal, M.; Lim, J. (2012)
Malaysia has shown strong desire to promote itself as a major biomass hub in the South East Asia region. Supportive policies such as the SREP and the National Renewable Energy Policy of 2010 have been introduced to enhance implementation and investment from the private sector. A discussion covers the green potential of palm industry in Malaysia; the R and D of palm biomass by governmental institutions and universities; development of palm biomass utilization and an evolution in the palm biomass industry; green policies in Malaysia to promote palm biomass; research in palm biomass promotion; opportunities of palm biomass; and the challenges for the development of the palm biomass industry. This is an abstract of a paper presented at the CHISA 2012 - 20th International Congress of Chemical and Process Engineering and PRES 2012 - 15th Conference PRES (Prague, Czech Republic 8/25-29/2012).